COVID-19 and rhino-orbital mucormycosis – A case report - Dilbag Singh; Harveen Kaur; N.C. Kajal (The Journal of Association of Chest Physicians, 2023)
There is a constant rise in cases of rhino-orbital mucormycosis in people with coronavirus disease 2019 (COVID-19). Generally, mucormycosis develops in immunosuppression or debilitating diseases. In cases having head and neck involvement, the mold enters the respiratory tract with further involvement of nose and sinuses and there is consecutive progression into orbital and intracranial structures. Diabetes mellitus (DM) is an independent risk factor for both severe COVID-19 and mucormycosis. The clinical examination and direct smears are helpful for early diagnosis of the disease and timely intervention. For the better prevention and management of such opportunistic infections in COVID-19 patients, it is prudent to establish prophylactic treatment protocols along with rational use of corticosteroids. We here report a case of rhino-orbital mucormycosis infection caused by Rhizopus oryzae in a COVID-19 patient with DM.